Employability model for students in increasing career opportunities - Binasari, Erni Suci; Tentama, Fatwa (Journal of Education and Learning (EduLearn), 2025)
The objective of this study was to create and develop an employability model, and the factors that influence be investigated in a proper environment. These students are working at STIE SBI Yogyakarta to determine the adequacy of the model's shape in considering the field-occurring factors. The population of this study was all active students at STIE SBI in Yogyakarta who are currently working. The sample in this study was 101 working STIE SBI students. The technique of sampling in this research used accidental sampling. The data collection instrument used a scale of employability, scale resilience, and the peer social support scale. Data analysis techniques in this study were carried out quantitatively. The analytical method used equation modeling partial least squares path modeling (SEM-PLS) 4.0 through testing the outer and inner models. This study's results were the formation of resilience and peer support models on the employability of working students who appropriate with empirical data. There is a positive and very significant effect of resilience on the employability of working students. The theoretical model formed in this study was an appropriate model that can be used as a valid model reference in developing employability variables.